A Study of the Chinese-English Translation of Exhibition Texts from the Perspective of Functional Equivalence Translation Theory - Li, Yi; Li, You; Jia, Miaomiao; Li, Yanbin; Wang, Chao (Advances in Social Sciences Research Journal, 2025)
The wave of economic globalization has made the exhibition industry increasingly prominent in national economic development, with China becoming the fastest-growing exhibition market globally. In this process, the translation of exhibition texts plays a crucial role. This study aims to focus on official bilingual exhibition texts from international fairs and expos such as the CIIE and CIEE over the past two years. Based on Nida’s theory of functional equivalence translation, it analyzes the three functions—language information, language expression, and language appeal—in exhibition English translation through specific examples. The study explores the translation strategies and principles required for exhibition text translation, which are of great practical significance both for the application and development of functional equivalence translation theory and for promoting better service to the exhibition economy through exhibition text translation.